2016
DOI: 10.15405/epsbs.2016.09.64
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Transformational Leadership in the Context of Education

Abstract: Following expansive changes in the management of schools and the methods of organizing the teaching as well as the changes in the styles of leadership as the function of management, contemporary approaches to leadership: transactional, charismatic, transformational and interactive become more often the focus of research interest. Each of these theoretical approaches has far-reaching impacts and values not only in time but also in a certain context. However, in this paper we give priority to transformational le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 21 publications
(28 reference statements)
0
13
0
1
Order By: Relevance
“…By studying relevant research on transformational leadership by Jovanovica & Ciric (2016), who studied the benefits of transformational leadership in the context of education, we found that the transformational leadership style is the most suitable for guiding the students within the school conditions. This type of claim has its basis in these three points: 1 ) the ethical dimension of transformational leadership, that is, the moral basis; 2 ) the validity of previous researches supported by evidence; and 3) evidence of the leaders' practice in the field of education.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…By studying relevant research on transformational leadership by Jovanovica & Ciric (2016), who studied the benefits of transformational leadership in the context of education, we found that the transformational leadership style is the most suitable for guiding the students within the school conditions. This type of claim has its basis in these three points: 1 ) the ethical dimension of transformational leadership, that is, the moral basis; 2 ) the validity of previous researches supported by evidence; and 3) evidence of the leaders' practice in the field of education.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…A transformational leader is expected to assess and satisfy the motives of individuals, values each one of them and their contributions to the success of their organization. As a result, transformational leadership style is frequently associated with improved work climate, commitment, effectiveness and employee job satisfaction (Jovanovica & Ciricb, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Jovanovic Dragana and Ciric Marina stated that transformational leadership is the most appropriate leadership to guide students in school conditions [36]. White Sarah K states transformational leadership is a leadership model in which leaders encourage, inspire and motivate employees to innovate and create changes that will help grow and shape future success in the company [37].…”
Section: Transformational Leadership In Overcoming Digital Dividementioning
confidence: 99%